The Relaxation-Mindfulness Competence of Secondary and High School students and its influence on classroom climate and academic performance (European Journal of Education and Psychology, 2018)
The aim of this work is twofold: first, to find out if there are differences by gender and academic level in relaxation and mindfulness competence in high school students. Second, it is intended to analyze the relation between Relaxation-Mindfulness, Classroom Climate and Academic Performance based on the hypothesis that classroom climate acts as a mediator between relaxation-mindfulness and academic performance. The study was conducted during an intervention of TREVA’s Relaxation-Mindfulness Program on a sample of 420 students of Compulsory Secondary School and High School with an average age of 14.29. The results showed no differences by gender in mindfulness but partially, by educational level. It was found that classroom climate acts as a mediator between mindfulness and academic performance. The implementation of programs of relaxation-mindfulness is highly recommended for Secondary and High School students.